The Palgrave handbook of anthropological ritual studies - Stewart, Pamela J.; Strathern, Andrew (Springer International Publishing, 2021)
1. Ritual Studies: Whence and Where to? (Andrew J. Strathern and Pamela J. Stewart) -- 2. Ritual Dream Sharing and Charismatic Church Routinization (Roger Ivar Lohmann) -- 3. Sacrifices in the Ancient World: Research on Complex Rituals (Günther Schörner) -- 4. Economic Thought, Ritual and Religion (Thomas Widlok) -- 5. Thanks For Your Visit, But You Can Go Now: Cortesia, hospitality and rites of distinction in Angola (Ruy Llera Blanes) -- 6. Formulas of Home: On the religious performance of personal rituals (Nigel Rapport) -- 7. Contesting Masculinity and Ritual Embodiment in Youth Baseball (John W. Traphagan) -- 8. Ritual, Performance and Cognition (Andrew J. Strathern and Pamela J. Stewart) -- 9. Grave-visiting rituals in Northwestern Europe (Anne Kjærsgaard and Eric Venbrux) -- 10. The Device of the Spirit Medium for connecting Humans to the Supernatural: A Case Study of Shamanic Healing in the Qorčin Region of Inner Mongolia, China (Saijirahu Buyanchugla) -- 11. Empathy and Ritual Practices (Anne Sigfrid Grønseth) -- 12. Ritual, Place, and Experience in Hindu Home-temple Visitation (Sanjoy Mazumdar and Shampa Mazumdar) -- 13. Designing Enchanted Rituals for Modern Man (Anne-Christine Hornborg) -- 14. Mo(nu)ments of Vulnerability: The Centrality of Ritual Creativity in Pilgrimages to Catholic Shrines in France and Portugal (Anna Fedele) -- 15. Rituals Surrounding Sorcery and Witchcraft in Traditional Societies: Issues for Researchers (G.W. Trompf) -- 16. On the Partiality of Pentecostal Ritual (Simon Coleman) -- 17. Infrastructures of Interrituality and the Aesthetics of Saint Veneration Rituals among Orthodox Christians and Arab Alawites in Hatay (Jens Kreinath) -- 18. Moka (ceremonial exchange) with Death (Pamela J. Stewart and Andrew J. Strathern). .